Developing countries in the WTO Dispute Settlement System - Hunter Nottage (University of Oxford, Global Economic Governance Programme (GEG), 2009)
One of the most noteworthy achievements of the establishment of the WTO in 1995 was the introduction of its binding dispute settlement system. Building upon GATT dispute settlement practice, the Understanding on the Rules and Procedures Governing the Settlement of Disputes ("DSU") contains innovations that resulted in a paradigm shift from a system based on economic power and politics to one based on the rule of law. The resulting increased legality of the WTO has been hailed to benefit considerably smaller countries, of which many are developing countries and least-developed countries ("LDCs"). As Steger and Hainsworth comment, the shift "is particularly beneficial for smaller countries, as without the rules and procedures of the DSU... they would not have the necessary bargaining power vis-à-vis the larger powers." Similarly, Weiler notes the advantages of the legalised WTO model, especially for the meek economically and politically unequal.
Keywords: 330